BIK polymorphism and proteasome regulation unveil host risk factor for severe influenza - Sourabh Soni; Soner Yildiz; Emma Kaitlynn Allen; Hans Petersen; Mark Peeples; Sara El Zahed; Lorena Rosas; Vandana Anang; Laura Antonescu; Richard Seonghun Nho; Ana Lucia Mora; Jeffrey Craig Horowitz; et al. (Proceedings of the National Academy of Sciences, 2025)
Influenza A viruses (IAVs) pose a significant public health threat, with host factors playing a crucial role in disease severity. We investigated the role of Bcl-2-interacting killer (BIK) in IAV infection using cellular and mouse models, and influenza-infected human cohort. In airway epithelial cells (AECs), BIK deficiency impaired viral replication, while BIK restoration enhanced it. Conversely, airway-specific BIK overexpression in mice increased viral load, inflammation, and mortality, whereas BIK suppression conferred protection. Critically, a genetic variation (rs738276) in the BIK gene, influencing BIK expression, correlates with altered viral replication in air–liquid interface differentiated primary normal human bronchial epithelial cells and influenza severity in humans. Mechanistically, we demonstrate that IAV nucleoprotein (NP) suppresses β5, a subunit of the proteasome, leading to increased BIK levels and enhanced viral replication. Conversely, β5 treatment dampened BIK levels and protected mice from IAV-induced morbidity and mortality. Furthermore, BIK interacts with NP, disrupting the Bcl-2/NP interaction and promoting viral replication. Our findings uncover an IAV–BIK–β5 axis that governs viral replication, suggesting that targeting BIK or β5 may offer therapeutic strategies against influenza.